Abundance and diversity of cotton insect pests under repeatedly cultivated cotton fields of Tanzania - Benjamin, Madama; Rwegasira, Gration M. (Frontiers in Insect Science, 2024)
Cotton production in Tanzania is facing significant challenges due to insect pests that cause extensive damages to the crop. The most notable pests include the African bollworm (Heliothis armigera Hubner), Spiny bollworm (Earias biplaga Walker), Cotton stainers (Dysdercus sidae (Herrich-Schaeffer), Cotton Aphids (Aphis gossypii Glover), Thrips (Thrips tabaci Lindeman), Jassids (Amrasca biguttula, Bigutula), Leafhoppers (Cicadellidae jassidae), and Whiteflies (Bemisia tabaci Genn). If left uncontrolled, these pests can cause up to 60% damage to the crop. Despite the importance of cotton and the fact that most of these pests are endemic, there are scanty knowledge on the dynamics and distribution of cotton pests across the seasons of the year and crop's phenological growth stages (germination, vegetative growth, flowering and boll formation) in areas under continuousrepeated cultivation of the crop in Tanzania. Here we report on the influence of seasons and cotton's phenological stages on the abundance, diversity, distribution and richness of cotton insect pests. The study was conducted in the Misungwi district for two cotton-growing seasons, using the UKM08 cotton variety. Stick traps and handpicking methods were deployed in catching the cotton insect pests. On average, more thana total of 8,500 insects specimen of diverse families and species were collected every season. The four dominant species among the collected were Aphis gossypii (17.37%), Amrasca biguttula (11.42%), Nezara viridura (10.7%), and Bemisia tabacci (10.68%). Both cotton phenological growth stages and seasons significantly (p< 0.05) influenced the abundance, diversity, distribution and richness of cotton insect pests. In particular, the phenological growth stage 3 exhibited greater diversity of insect pests. The pests' distribution patterns remained relatively uniform across the crop growth stages. Findings from the present study could contribute to developing sustainable pest management strategies in areas under continuousrepeated cotton production in Tanzania and elsewhere.